Effects of Astragalus fasciculifolius gum on wound healing in streptozotocin-induced diabetic rats - Mohammadali Ayubi-Rad; Soheila Yosefi; Mohammadreza Hajizadeh; Hamidreza Jafari-Naveh; Mahsa Hassanipour; Fatemeh Alamchi; Afsaneh Fadai; Faridehsadat Khorasani; Farzanehsadat Hosseini; Mahdieh Bemani; Mehdi Mahmoodi (Shahrekord University of Medical Sciences, 2020)
Introduction: Recently it has been shown that Astragalus fasciculifolius may be an effective remedy in the treatment of diabetes and wound healing. Current study was designed to examine the effects of topical administration of A. fasciculifolius (common name: sarcocolla) cream on treatment of wounds in streptozotocin-induced diabetic rats. Methods: A circle deep wound having 15-mm diameter was created on the back of 32 streptozotocin-induced diabetic rats. Thirty-two wounds were evaluated in four groups of animals (n = 8). The animals in first and second groups were treated using distilled water and petrolatum for 20 days, respectively. The third and fourth groups were treated using sarcocolla cream 5% and 10% for 20 days, respectively. The evaluation was performed in all groups on days 1, 3, 5, 7, 10, 14, 17 and 20. Results: The sarcocolla cream 5% and sarcocolla cream 10% exerted significant healing effects on diabetic rat wounds (P<0.001) compared to the control groups under treatment of petrolatum or distilled water. The sarcocolla cream had favorable effects on the woundhealing ratio especially during long-term (14 days), with no difference at concentrations of sarcocolla 5% and 10%. Conclusion: Sarcocolla (topical) therapy is possibly a useful approach for wound healing in diabetic rats. More investigations are needed to elucidate the possible protective mechanisms and safety.